2022
DOI: 10.1017/s095026882100279x
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of Mycobacterium tuberculosis for prediction of drug resistance

Abstract: Whole-genome sequencing (WGS) has shown tremendous potential in rapid diagnosis of drug-resistant tuberculosis (TB). In the current study, we performed WGS on drug-resistant M. tuberculosis isolates obtained from Shanghai (n=137) and Russia (n=78). We aimed to characterize the underlying and high-frequency novel drug resistance-conferring mutations, and also create valuable combinations of resistance mutations with high predictive sensitivity to predict multidrug-and extensively drug-resistant tuberculosis (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…Although these methods are rapid and straightforward, Mtb continuously evolves through the genomic acquisition of single nucleotide polymorphisms (SNPs), insertions, and deletions (indels), impacting the ability to discriminate strains without the classic regions used for resistance detection [20]. Wholegenome sequencing (WGS), as a molecular diagnostic tool, has been greatly developed in TB research and is clinically useful for predicting drug resistance, lineage, tracing transmission, and defining outbreaks [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods are rapid and straightforward, Mtb continuously evolves through the genomic acquisition of single nucleotide polymorphisms (SNPs), insertions, and deletions (indels), impacting the ability to discriminate strains without the classic regions used for resistance detection [20]. Wholegenome sequencing (WGS), as a molecular diagnostic tool, has been greatly developed in TB research and is clinically useful for predicting drug resistance, lineage, tracing transmission, and defining outbreaks [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, interesting large deletions related to the pncA and gid genes were detected.In turn, non-resistance-conferring mutations were detected in the katG (R463L) and gyrA (E21Q, S95T, G668D) genes that may be useful for the evolutionary characterization of the M. tuberculosis genome. (8,53).…”
Section: Discussionmentioning
confidence: 99%
“…Inside all diagnostic innovations in TB for resistance detection, it has been shown that WGS as a molecular diagnostic tool can be used to detect/rule out resistance to all drugs simultaneously (6)(7)(8). It also allows lineage identification, transmission tracing and outbreak definition (7)(8)(9)(10)(11) and is a faster and more effective method than traditional phenotypic DST (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that Beijing strain was positively correlated with this phenotype, isoniazid resistance, reported to be mainly related to the katG gene mutations[ 59 ]. This is similar to the findings of studies in a whole-genome sequencing based study in China[ 60 ], of which 1024 MDR strains were identified from 2019 strains of Mycobacterium tuberculosis .…”
Section: Discussionmentioning
confidence: 99%